ETNOMATHEMATICS: EXPLORATION OF THE ART OF KENTHONGAN MUSIC AS A SOURCE OF MATHEMATICS LEARNING - Fitria Zana Kumala; Zaenurrohman Zaenurrohman; Nurul Ma’unah; Gunawan Gunawan (International Journal of Multidisciplinary Research and Literature, 2022)
Ethnomathematics is an approach tio learning mathematics that connects the material studied with the local culture of students. Ethnomathematics can be used by mathematics educators to overcome problems in the field of mathematics, namely the negative perception of students about mathematics which is seen as difficult. This study aims to explore, identify, describe and analyze mathematical concepts contained in the art of kenthongan music. This research is a qualitative descriptive exploratory research with an ethnographic approach. Data were collected by observation, documentation, and interviews. This research was conducted on the kenthongan music art group "Syailendra". The analytical technique used is the Miles and Huberman model and the data validity test uses triangulation. This study shows that there are mathematical concepts found in the art of kenthongan music, especially in the kenthongan art group "Syailendra" which can be used as learning resources in learning mathematics. The mathematical concepts found include the concept of geometry in which there is the concept of a circle and the concept of a tube, then there is the concept of natural numbers and the concept of arithmetic sequences. Furthermore, universal mathematical activities such as counting, locating, measuring, designing, playing, and explaining activities were also found